Environmental Management Expenditure and Fiscal Sustainability of South African Urban Municipalities: A Panel Data Model - Silas Mukwarami; Huibrecht M van der Poll (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Globally, instituting good environmental management practices within cities in developing countries is a climate-induced risk mitigation strategy. It is, however, an opportunity for local municipalities to achieve fiscal sustainability objectives and environmentally responsible decisions. Cash-constrained local municipalities are characterized by failures to balance environmental and financial needs, resulting in complex urban sustainability challenges. Therefore, this article examines the relationship between environmental management expenditure and fiscal sustainability (FS) in South African local municipalities to contribute to the debate concerning the sustainability of environmental protection projects in local municipalities. The study employed ordinary least squares and feasible generalized least squares to estimate coefficients of linear regression equations involving data collected from 30 local municipalities from 2012 to 2021. The results suggest that only wastewater and environmental protection expenditures positively impact FS, with solid waste management expenditure influencing the FS negatively. Lessons from the research will assist policymakers and municipal administrators in addressing environmental policy incoherence for the improved financial viability of environmental protection projects. Lastly, future research can focus on environmental data collection and reporting for improved and informed environmental protection decisions.